Reorganization of Visual Callosal Connections Following Alterations of Retinal Input and Brain Damage - Restani, Laura; Caleo, Matteo (Frontiers in Systems Neuroscience, 2016)
Vision is a very important sensory modality in humans. Visual disorders are numerous and arising from diverse and complex causes. Deficits in visual function are highly disabling from a social point of view and in addition cause a considerable economic burden. For all these reasons there is an intense effort by the scientific community to gather knowledge on visual deficit mechanisms and to find possible new strategies for recovery and treatment. In this review we focus on an important and sometimes neglected player of the visual function, the corpus callosum (CC). The CC is the major white matter structure in the brain and is involved in information processing between the two hemispheres. In particular, visual callosal connections interconnect homologous areas of visual cortices, binding together the two halves of the visual field. This interhemispheric communication plays a significant role in visual cortical output. Here, we will first review essential literature on the physiology of the callosal connections in normal vision. The available data support the view that the callosum contributes to both excitation and inhibition to the target hemisphere, with a dynamic adaptation to the strength of the incoming visual input. Next, we will focus on data showing how callosal connections may sense visual alterations and respond to the classical paradigm for the study of visual plasticity, i.e. monocular deprivation. This is a prototypical example of a model for the study of callosal plasticity in pathological conditions (e.g. strabismus and amblyopia) characterized by unbalanced input from the two eyes. We will also discuss findings of callosal alterations in blind subjects. Noteworthy, we will discuss data showing that inter-hemispheric transfer mediates recovery of visual responsiveness following cortical damage. Finally, we will provide an overview of how callosal projections dysfunction could contribute to pathologies such as neglect and occipital epilepsy. A particular focus will be on reviewing noninvasive brain stimulation techniques and optogenetic approaches that allow to selectively manipulate callosal function and to probe its involvement in cortical processing and plasticity. Overall, the data indicate that experience can potently impact on transcallosal connectivity, and that the callosum itself is crucial for plasticity